Bi-objective operation optimization of regional integrated energy system considering shared energy storage - Li, Xiaobang; Zhu, Liying; Zhao, Liying; Zhang, Kang (Scientific reports, 2025)
With the development of the sharing economy, the concept of “sharing” has begun to penetrate into the power grid, and companies have begun to explore service models for shared energy storage. Based on this, this article studies the optimization technology of regional integrated energy system (RIES) operation considering shared energy storage, which is conducive to promoting China’s energy strategy transformation, improving energy utilization efficiency and energy system flexibility. Firstly, the RIES fundamental structure integrating shared energy storage is constructed; Secondly, operational optimization objectives are established for both the RIES and the energy storage aggregator (ESA), aiming to minimize their respective operating costs. The constraints of the operational optimization model are analyzed; Based on the traditional sparrow search algorithm, the chaos sparrow search algorithm (COSSA) is constructed by combining Tent chaos and Gaussian mutation. Last, an illustrative case study demonstrates the effectiveness of the proposed model, showcasing a reduction in RIES operating costs of 2.912536 million dollars enabled by shared energy storage participation. As a result, our method facilitates a more efficient operation of RIES.